Poluição como temática para construção do conhecimento químico de reações redox sob uma perspectiva CTSA - Klein, Sabrina Gabriela (2016)
In search of a distinctive chemical education, with meaning for social and productive life of young high school students, the present study investigates how the theme "pollution" may facilitate the construction of the teaching and learning process of redox reactions content of high school students under a STSE (Science-Technology-Society-Environment) approach. For this, firstly, we sought theoretical references about the conceptual part of redox reactions and the theme "pollution". Then, we conducted an analysis of papers published in the journal Chemistry at the New School , with the intention of investigating how the redox reactions have been explored, their different approaches and their impact on the teaching of chemistry. From this, we developed a proposal to approach the redox reactions in the classroom, which was assessed through interventions with the second year high school students from a public school of Santa Maria, RS. Interventions in the classroom were carried out in two steps, both based on the methodology of the three pedagogical moments. The first developed inorganic redox content associated with the pollution of soil, whereas the second involved some organic redox reactions through the water pollution, specifically the treatment of effluents. This is a qualitative research. To collect data, we use questionnaires and textual productions, they were analyzed according to the Discursive Textual Analysis. The results allowed us to conclude that the development of redox reactions associated with the theme "pollution" by a STSE perspective favored teaching and learning of chemistry, as we observe an improvement in the construction of students knowledge.